2017
DOI: 10.1111/maq.12372
|View full text |Cite
|
Sign up to set email alerts
|

Guadalupan Devotion as a Moderator of Psychosocial Stress among Mexican Immigrants in the Rural Southern United States

Abstract: This study considers how shared devotion to the Virgin of Guadalupe among Mexican immigrants in rural Mississippi buffers the effects of immigration stress. Rural destinations lacking social services can quickly compound the already stressful experience of immigration. Guadalupe devotion provides a way of coping with the daily life stressors of immigration. We test the hypothesis that high consonance in the cultural model of Guadalupan devotion will moderate the adverse health effects of immigration stress. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
(54 reference statements)
0
4
0
1
Order By: Relevance
“…These chronic assaults on the body lead to a higher allostatic load, which over a lifetime, lead to poor health [23,45]. For example, in a study of Hispanic immigrants in a southern town, Read-Wahidi and DeCaro found that immigrants who were more consonant with a cultural model of devotion to the Virgin of Guadalupe (a highly salient form of devotion in Mexico) were buffered from the effects of immigration stressors on psychological distress [46]. The current study looks at a similar population and considers how consonance with a more general domain of lifestyle impacts depressive symptomatology.…”
Section: Theoretical Orientation: Cultural Consonancementioning
confidence: 99%
“…These chronic assaults on the body lead to a higher allostatic load, which over a lifetime, lead to poor health [23,45]. For example, in a study of Hispanic immigrants in a southern town, Read-Wahidi and DeCaro found that immigrants who were more consonant with a cultural model of devotion to the Virgin of Guadalupe (a highly salient form of devotion in Mexico) were buffered from the effects of immigration stressors on psychological distress [46]. The current study looks at a similar population and considers how consonance with a more general domain of lifestyle impacts depressive symptomatology.…”
Section: Theoretical Orientation: Cultural Consonancementioning
confidence: 99%
“…Second, in this study social support was not related to household fear of deportation or sUA levels, despite other research (Thomas et al, 1985) finding that stronger social support was related to lower serum UA levels, independent of age and weight. For the future, we will consider examining whether other protective factors may mitigate the effect of fear of deportation on salivary biomarkers, such as religious coping (Read-Wahidi & DeCaro, 2017) and civic engagement. The social support scale we used may not capture other ways that members of mixed-status Latino families receive support from others in the context of restrictions shaped by local immigration enforcement policies.…”
Section: Discussionmentioning
confidence: 99%
“…Una identidad no necesariamente reemplaza a la otra (Santiago-Irizarry, 2008). El medio para lograrlo es la llamada Iglesia transnacional: permite el acceso al capital social en el país anfitrión y la retención del capital social en su país de origen (Soto, 2012); la congruencia con la devoción religiosa que se practique (Read-Wahidiy & DeCaro, 2017).…”
Section: Reducir Vulnerabilidades: Primero Subjetivas Luego Objetivasunclassified